Specific intellectual, modern society and change - Zulfiqar Ali, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2012)
This essay is written in pursuance of two tasks. First, it would challenge Marx‟s notion of „universal intellectual‟ from the perspective of Foucault‟s „specific intellectual‟. It is argued that Marx‟s universal intellectual is a political construction. It is flawed on account of its limited scope and deceptive understanding of modern society. Additionally and necessarily it is argued that Foucault‟s idea of „specific intellectual‟ is relatively strong and viable in the context of modern society. The second task of this paper is to defend Foucault‟s position against the charge leveled by Hoy and McCarthy that the notion of specific intellectual is highly individualistic and personal. The movement based upon this notion would necessarily fail to make appeal to the public. I argued that, in spite of being specific, intellectual can make appeal to the affected ones to bring about, of course not the global but local changes at precise points.